2015
DOI: 10.1088/0953-2048/28/9/095012
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic properties of a single superconducting CaCuO2/SrTiO3interface

Abstract: The transport properties of CaCuO2/SrTiO3 single interfaces are studied by resistance versus temperature measurements in external magnetic fields. The superconducting anisotropy where and are the superconducting coherence lengths parallel and perpendicular to the interface, respectively, shows values higher than that previously obtained for CaCuO2/SrTiO3 superlattices deposited in the same conditions. The larger anisotropy, observed for the single interfaces, indicates that the charge carriers are confin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
2
0
1
Order By: Relevance
“…where H c ab 2 and H c c 2 are the upper critical fields along the a-b plane (the plane of the substrate) and the c-axis (perpendicular to the substrate surface), respectively. The resistance as a function of temperature in different magnetic field has been measured in CCO/STO SLs [39] and a CCO/STO bilayer [40]. The results, reported in figure 10, show that the superconducting anisotropy is about three to four times larger in a CCO/STO bilayer (γ≈17-18), where there is no interlayer interaction, than in CCO/STO SLs (γ≈5-7).…”
Section: Cacuo 2 /Srtiomentioning
confidence: 99%
“…where H c ab 2 and H c c 2 are the upper critical fields along the a-b plane (the plane of the substrate) and the c-axis (perpendicular to the substrate surface), respectively. The resistance as a function of temperature in different magnetic field has been measured in CCO/STO SLs [39] and a CCO/STO bilayer [40]. The results, reported in figure 10, show that the superconducting anisotropy is about three to four times larger in a CCO/STO bilayer (γ≈17-18), where there is no interlayer interaction, than in CCO/STO SLs (γ≈5-7).…”
Section: Cacuo 2 /Srtiomentioning
confidence: 99%
“…而得到了穹顶状的 T c -调控电压关系曲线 [52] 。这与之前在薄膜中发现的无序驱 动的超导-绝缘体量子相变类似 [53] ,所以他们认为这也是一种由无序驱动的效 相近 [55,56] 。但对于 KTO,化学掺杂的 KTO 体材料上并未发现超导,然而研究 者们通过电双层(electric double layer ,EDL)晶体管调控,在 KTO(001)表 面得到 T c 在 50 mK 左右的超导 [57] ,同时利用离子液体(ionic liquid ,IL 组成,其超导发生在铜氧层上。铜氧化物超导体的母体一般是反铁磁绝缘体 [59] , 可以通过掺杂来压制反铁磁序从而获得超导,但当掺杂量的进一步增加,超导 消失,材料进入费米液体态,整个超导区域随着掺杂的变化呈一个穹顶状。对 于铜氧化物超导体而言,T c 和单个元胞内铜氧面层数成正相关 [60] ,而且很多铜 氧化物超导体的 T c 都远超 BCS 理论所得到的麦克米兰极限,所以一般认为铜 氧化物超导体是非常规超导体。同时铜氧化物超导的电子配对对称性也不是常 规超导体的 s 波配对,现阶段接受最广泛的是𝑑 𝑥 2 −𝑦 2 配对 [61] 。目前 2DEG 界面 超导 T c 最高只有 2. 研究发现其面内和面外的上临界场具有明显的各向异性 [66,67]…”
Section: 一个非常经典的理论:在有杂质的情况下(现实中任何材料都有杂质) ,足够大unclassified
“…The effect of interface on superconductivity has received much attention. It was demonstrated that superconductivity can occur at the interface of two nonsuperconducting materials [1][2][3][4][5][6], and the critical temperature (T c ) can even be significantly enhanced com-pared with the corresponding single-phase samples [1,[7][8][9]. One of the most intriguing interfaces is the bilayer of La 2 CuO 4 and La 2−x Sr x CuO 4 [LSCO(x)] films.…”
Section: Introductionmentioning
confidence: 99%